High Density Salt and Pepper Noise Removal in Images Using Adapted Decision Based Unsymmetrical Trimmed Mean Filter Cascaded with Gaussian filter (International Journal of Engineering and Computer Science, 2015)
An adapted decision based unsymmetrical trimmed mean filter cascaded with Gaussian filter (ADCG) algorithm for the retrieval of gray scaled image which is induced by a very high density Salt and Pepper (impulse) noise is proposed and tested in this paper. The proposed calculation supplants the noisy pixel by trimmed mean quality when other pixel values, 0's and 255's are available in the selected window and when all the pixel qualities are 0's and 255's then the noisy pixel is supplanted by mean estimation of the considerable number of components present in the selected window. This proposed methodology shows preferred results over the Standard Median Filter (MF), Decision Based Algorithm (DBA), Modified Decision Based Algorithm (MDBA), Progressive Switched Median Filter (PSMF) and Modified Decision Based Unsymmetrical Trimmed Median Filter (MDBUTMF). The proposed methodology is tried against distinctive pictures and it gives better PSNR that is Peak Signal-to-Noise Ratio.